(untitled) (Journal of the College of Basic Education, 2022)
Religion had a great and important place among the ancient Moroccans, as did the Phoenician immigrants. The names that the Carthaginians carried indicate this, such as “Shafut Baal, meaning Baal spent, Hannibal, meaning he was favored by Baal, and others, and this seems clear through archaeological and cultural remains such as temples and tombs discussions, and so on.The Phoenician immigrants had continued to worship the Phoenician gods, and they maintained for a long time the Phoenician religious customs, and they quickly adopted local deities in the ancient Maghreb as well as for the Moroccans. In addition to the god Melgart, the god of Tyre, as well as the god Echmoun, a native of Africa, most of them were worshiped by the ancient Moroccans.In this intervention, we want to shed light on the most prominent Phoenician Carthaginian deities in the ancient Maghreb and their position among the Carthaginians and Moroccans, in addition to highlighting the Phoenician-Carthaginian religious influence on the ancient Moroccans, who sanctified them, so they became religious centers of worship in the ancient countries of the Maghreb, where they practiced their worship and religious rituals.